Phase 1 Randomized Study of a Tetravalent Dengue Purified Inactivated Vaccine in Healthy Adults in the United States - Schmidt, Alexander C.; Lin, Leyi; Martinez, Luis J.; Ruck, Richard C.; Eckels, Kenneth H.; Collard, Alix; De La Barrera, Rafael; Paolino, Kristopher M.; Toussaint, Jean-François; Lepine, Edith; Innis, Bruce L.; Jarman, Richard G.; et al. (The American journal of tropical medicine and hygiene, 2017)
The safety and immunogenicity of four formulations of an investigational tetravalent dengue purified inactivated vaccine (DPIV), formulated at 1 or 4 μg with aluminum hydroxide (alum) or at 1 μg with an adjuvant system (AS01 E or AS03 B ), were evaluated in a first-time-in-human, placebo-controlled, randomized, observer-blind, phase 1 trial in the continental United States. Two doses of vaccine or placebo were administered intramuscularly 4 weeks apart to 100 healthy adults 18–39 years of age, randomized 1:1:1:1:1 to receive one of four DPIV formulations or saline placebo. The response to a third dose was evaluated in a subset of nine participants remote from primary vaccination. Humoral immunogenicity was assessed using a 50% microneutralization assay. All DPIV formulations were well tolerated. No vaccine-related serious adverse events were observed through 12 months after the second vaccine dose. In all DPIV groups, geometric mean antibody titers peaked at Day 56, waned through 6 months after the second vaccine dose, and then stabilized. In the nine subjects where boosting was evaluated, a strong anamnestic response was observed. These results support continuation of the clinical development of this dengue vaccine candidate (clinicaltrials.gov: NCT01666652).